Advancements in the Treatment of Mucopolysaccharidoses: From Established Therapies to Gene Therapy - Wanat, Joanna; Homa, Wojciech; Warunek, Aleksandra; Gronowicz, Gabriela; Dzikowska , Izabela; Siejka , Agata; Stefaniak, Daria; Zielińska , Weronika; Chról, Michał (Journal of Education, Health and Sport, 2025)
Introduction and purpose Mucopolysaccharidoses (MPS), a subset of inborn errors of metabolism (IEM), are genetic disorders requiring pediatricians to recognize non-specific symptoms and carefully monitor newborns. Early diagnosis is essential for optimizing therapeutic outcomes. In recent years, significant progress has been made not only in the diagnostic process but also in the development of therapies. Established treatments, such as hematopoietic stem cell transplantation (HSCT) and enzyme replacement therapy (ERT), have been improved, while advancements in gene therapy have opened new possibilities. State of knowledge Numerous studies and clinical trials suggest that novel therapies could be game-changers in managing MPS. Among the promising new treatments are: blood-brain barrier (BBB)-penetrable enzyme replacement therapy (ERT), substrate reduction therapy, nonsense suppression therapy, and mRNA engineering. However, the most advanced treatments, that are currently under investigation are in-vivo and ex-vivo gene therapy. Conclusions This article aims to review treatment options for MPS I (Hurler syndrome), highlighting the evolution from established therapies to innovative approaches.